Iron Therapeutics in Women's Health: Past, Present, and Future - Joel Mintz; Jackie Mirza; Eric Young; Kyle Bauckman (MDPI AG, 2020)
Iron plays a unique physiological role in the maintenance of homeostasis and the pathological outcomes of the female reproductive tract. The dual nature of elemental iron has created an evolutionary need to tightly regulate its biological concentration. The female reproductive tract is particularly unique due to the constant cycle of endometrial growth and shedding, in addition to the potential need for iron transfer to a developing fetus. Here, iron regulation is explored in a number of physiologic states including the endometrial lining and placenta. While iron dysregulation is a common characteristic in many women's health pathologies there is currently a lack of targeted therapeutic options. Traditional iron therapies, including iron replacement and chelation, are common treatment options for gynecological diseases but pose long term negative health consequences; therefore, more targeted interventions directed towards iron regulation have been proposed. Recent findings show potential benefits in a therapeutic focus on ferritin-hepcidin regulation, modulation of reactive oxygen species (ROS), and iron mediated cell death (ferroptosis). These novel therapeutics are the direct result of previous research in iron's complex signaling pathway and show promise for improved therapy, diagnosis, and prognosis in women's health.